Peran Pemberdayaan Sumber Daya Manusia dalam Peningkatan Kinerja Organisasi melalui Perubahan dan Resiliensi Organisasi (Studi pada Industri Perhotelan di Jawa Timur) - Boge Triatmanto; Djumilah Zain; Eka Afnan Troena; Mintarti Rahayu (Jurnal Aplikasi Manajemen, 2012)
The Objectives of this research are to examine and to provide empirical on about the influence of human resource empowerment, directly and indirectly, through organizational change as well as its ability in adapting to change. In details, the objectives of the research are as follow: (1) Human Resources Empowerment toward organizational change, (2) Human Resources Empowerment toward organizational resilience, (3) Human Resources Empowerment toward performance organization, (4) Organizational resilience toward organizational change, (5) Organizational resilience toward organization performance, and (6) Organizational change toward performance organization. The results of this research, is expected to be able to enrich the knowledge of management, especially on the development of human resource management and organization. Therefore, this study will hopefully be useful will be useful for both academicians and practitioners. The population of this research is 69 star hotels, in East Java and 34 hotels as the samples using proportional sampling method. The respondents of this research are 216 hotel managers. The main findings of this research showed that the performance the organization performance is improved when the human resource is empowered is participation to achieve goals, commitment, and greater authorities and responsibilities in decision making process. Greater influence is achieved when the organization is able to adapt to the change of the hotels’ environment.Keywords: Human Resources Empowerment, Performance of Organization, Organizational Change, Organizational Resilience